A systematic review and meta‐analysis of randomized controlled trials comparing hysteroscopic morcellation with resectoscopy for patients with endometrial lesions. Issue 1 (7th November 2016) - Li, Chunbo; Dai, Zhiyuan; Gong, Yuping; Xie, Bingying; Wang, Bei
Abstract: Background: Results on the efficacy of hysteroscopic morcellation for patients with endometrial lesions remain conflicting. Objectives: To compare hysteroscopic morcellation with conventional resectoscopy for removal of endometrial lesions. Search strategy: Electronic databases were searched for reports published up to February 1, 2016, using terms such as "morcellator, " "morcellators, " "morcellate, " "morcellation, " "morcellated, " "hysteroscopy, " "hysteroscopy, " "uteroscope, " and "transcervical." Selection criteria: Randomized controlled trials were included if they assessed success rate, procedure speed, complications, tolerability, and/or learning curve. Data collection and analysis: Data were extracted by two independent reviewers and a meta‐analysis was performed. Main results: Four trials including 392 patients were analyzed. Successful removal of all endometrial lesions was more frequent with hysteroscopic morcellation than conventional resectoscopy (odds ratio 4.49, 95% confidence interval [CI] 1.94–10.41; P <0.001). Total operative time was also shorter with hysteroscopic morcellation (mean difference −4.94 minutes, 95% CI −7.20 to −2.68; P <0.001). No significant differences in complications were found. Meta‐analyses were not possible for tolerability and learning curve. In one study, hysteroscopic morcellation was acceptable to more patients ( P =0.009). Conclusions: Hysteroscopic morcellation is associated with a higher operative success rate and a shorter operative time among patients with endometrial lesions than is resectoscopy. More high‐quality trials are required to validate these results. Abstract : Hysteroscopic morcellation is associated with a higher operative success rate and a shorter operative time among patients with endometrial lesions than is resectoscopy.